EIB Working Paper 2021/12 Complementarities in capital formation and production - European Investment Bank (European Investment Bank, 2021)
Using macro and firm-level data, this paper investigates the complementarities between investment in different types of tangible assets such as machinery and buildings, and intangible assets such as software, training of employees, and business process improvements. It finds that investment in different assets types tends to be complementary, improving firm performance. Policy measures should address investment bottlenecks arising from market imperfections, while leaving it to the firm to find the most appropriate mix of assets.